THE EFFECT OF DIGITAL LITERACY ON KNOWLEDGE SHARING INTENTION OF EMPLOYEES IN YOGYAKARTA AND WEST JAVA - Sophie Johanna Panget; Agus Gunawan; Yoke Pribadi Kornarius; Angela Caroline (Jurnal Administrasi Bisnis, 2024)
The rapid advancement of digital technologies has strengthened the strategic importance of digital literacy in fostering knowledge‐sharing behavior within organizations. This study examines the effect of digital literacy on employees’ knowledge‐sharing intention in Kota Yogyakarta and Kota Bandung, two major urban centers in Indonesia. A mixed‐methods approach was employed, involving 60 respondents through questionnaire surveys supported by narrative analysis. Quantitative data were analyzed using validity and reliability tests and simple linear regression. The results indicate that digital literacy has a significant positive influence on knowledge‐sharing intention. Furthermore, employees in Kota Bandung exhibit higher knowledge‐sharing intention compared to those in Kota Yogyakarta, suggesting contextual differences in digital readiness and knowledge culture. These findings highlight the need for organizations to strengthen continuous digital literacy initiatives as a strategy to enhance collaborative knowledge practices in the workplace.